A Holistic Approach to Enhancing the Quality of Education for Inclusive Students in Elementary Schools - Rijal, Muhammad Syamsul; Badrun, Ahmad; Syakaqi, Abdur Rahman (Journal of Education and Social Science, 2025)
Inclusive education in elementary schools is an important effort to ensure that every student, including those with special needs, gets equal educational rights. This article examines a holistic approach in improving the quality of education for inclusive students, with an emphasis on collaboration between educators, parents and the community. A holistic approach includes various aspects, such as curriculum adaptation, development of inclusion-friendly teaching methods, teacher training, and creating a learning environment that supports diversity. This research uses qualitative methods with literature analysis and case studies in several inclusive elementary schools. The study results show that a holistic approach can improve learning motivation, student engagement, and their academic outcomes. Thus, implementing this approach is recommended as an effective strategy to support sustainable and quality inclusive education at the elementary school level.